Who is in favor of affirmative action? Representative evidence from an experiment and a survey - Sabrina Herzog; Hannah Schildberg-Hörisch; Chi Trieu; Jana Willrodt (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2023)
Although affirmative action remains controversial, little is known about who supports or opposes it and why. This paper investigates preferences for affirmative action by combining causal evidence from an experiment on the role of self-serving motives and in-group favoritism with survey data on three different affirmative action policies. Our results rely on a population-representative sample from the US. We find that support for affirmative action is based both on self-serving motives and principled grounds (e.g., related to an individual's altruism, fairness perceptions, concerns for efficiency, and political views). By contrast, in-group favoritism and socio-demographic characteristics play a much smaller role.
Keywords: C99; D01; D63; J78; 330; support for affirmative action; self-serving motives; in-group fa-voritism; altruism; efficiency; fairness; discrimination